A Catastrophe Theory of Union Behaviour - Eastman, Byron (Relations Industrielles / Industrial Relations, 1985)
This paper develops a catastrophe model of union behaviour. It presents an explanation of the unexpected character of some work stoppages as well as for the breakdown of negotiations which appeared headed for resolution.